Preparation of Silicon Nitride Nanowires and Dielectric Properties - Chen, Jin; Wang, Xiaogang (Asian Journal of Chemistry, 2013)
Using carbon nanotubes as template to prepare solid silicon nitride nanowires. The reaction was carried out in ammonia atmosphere. Silicon and SiO2 were used as starting materials. The structure, phase composition, dielectric properties and oxidation resistance of the sample were investigated. The results showed that the sizes of the nanorods are 60-80 nm in diameter and up to several microns in length. In the products a-Si3N4 is the main component. Due to nano-material’s quantum size effects, the FTIR spectra of the silicon nitride nanowires have blue shift phenomena. The sample shows good oxidation resistance in high temperature. The dielectric constants decrease with the increasing measuring frequency. The dielectric constants reduced from 9 (10 KHz) to 6.9 (100 MHz) at room temperature.